2009
DOI: 10.1186/1755-1536-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Focus on collagen: in vitro systems to study fibrogenesis and antifibrosis _ state of the art

Abstract: Fibrosis represents a major global disease burden, yet a potent antifibrotic compound is still not in sight. Part of the explanation for this situation is the difficulties that both academic laboratories and research and development departments in the pharmaceutical industry have been facing in re-enacting the fibrotic process in vitro for screening procedures prior to animal testing. Effective in vitro characterization of antifibrotic compounds has been hampered by cell culture settings that are lacking cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 84 publications
(112 reference statements)
4
100
1
Order By: Relevance
“…LOX inhibition also can render collagen more susceptible to degradation 50 ; however, we could not detect any change in collagen protein levels or degradation (measured by quantitating hydroxyproline levels) in BAPN-treated mice. On the other hand, past studies have shown that even a partial inhibition of collagen crosslinking results in changes in aortic wall stiffness 51,52 .…”
Section: Discussioncontrasting
confidence: 38%
“…LOX inhibition also can render collagen more susceptible to degradation 50 ; however, we could not detect any change in collagen protein levels or degradation (measured by quantitating hydroxyproline levels) in BAPN-treated mice. On the other hand, past studies have shown that even a partial inhibition of collagen crosslinking results in changes in aortic wall stiffness 51,52 .…”
Section: Discussioncontrasting
confidence: 38%
“…Fibroblasts were cultured on a 10-cm dish until confluent. The medium was then changed to DMEM containing 5% FBS, 100 μM l-ascorbic acid with 500 kDa dextran sulfate at 100 μg/ml, and 50 ng/ml recombinant human LOXL2 for 7 days (36,37). The cell layer was extracted with 0.5 M acetic acid and 0.1 mg/ml pepsin overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…in monomeric collagens then undergo a series of spontaneous condensation reactions that result in the formation of intra-and intermolecular covalent collagen cross-links (35). We first established an assay of collagen cross-linking induced by recombinant LOXL2 (36,37) and found that corilagin and all other trihydroxyphenolics tested prevented cross-linking (IC 50 = 10 nM; Supplemental Figure 3, A-C) whereas an inhibitor of TGF-β1 signaling (SB431542) and an antioxidant (N-acetylcysteine) had no effect ( Figure 3B). LOXL2 enzymatic activity toward a model substrate was assessed monitoring H 2 O 2 release.…”
Section: Phenotypic Screen Identifies Small Molecules With Antifibrotmentioning
confidence: 99%
“…For the detection of collagen deposition, L-ascorbic acid 2-phosphate (Sigma-Aldrich Corp.) was added to the TM cell medium to allow collagen maturation. 40 Ninety-six hours after cell treatment with the various compounds tested, TM cells were fixed either with ice-cold methanol for the detection of collagen deposition or fibronectin, or with 4% paraformaldehyde for the detection of actin stress fibers, a-SMA, and vinculin. The cells were treated with 0.1% Triton X-100 and 3% normal goat serum (NGS) for 1 hour and then incubated overnight at þ48C with relevant antibodies in a 1% NGS solution.…”
Section: Immunocytochemistrymentioning
confidence: 99%